Harvest and nutrient management in black henbane (Hyocyamus niger) on sodic soil - Singh, Ajai; Singh, Bajrang (The Indian Journal of Agricultural Sciences, 2005)
A field experinlent was conducted from 2000-2001 and 2001-2002 during 2 crop seasons at Banthra farm of the lnstitute at Lucknow to study the harvest and nutrient management on henbane (Hyocyamus niger L.) on semi-reclaimed sodic soils. Results showed that harvesting at 50% flowering recorded the highest herbage yield ( 1750 and 1880 kg/ha) and alkaloid content (0.12 and 0.14%) and among the nutrient management. Celrich (bioorganic soil enricher) fetched the significantly highest herbage yield of 48 and 9% over the control and N60, P40, treatments respectively. Accordingly the alkaloid content also increased by Celrich to 49% and 16% from the control and N60, P40, treatments. Although interaction effects were non-significant.